2015
DOI: 10.3390/e17010368
|View full text |Cite
|
Sign up to set email alerts
|

Message Authentication over Noisy Channels

Abstract: The essence of authentication is the transmission of unique and irreproducible information. In this paper, the authentication becomes a problem of the secure transmission of the secret key over noisy channels. A general analysis and design framework for message authentication is presented based on the results of Wyner's wiretap channel. Impersonation and substitution attacks are primarily investigated. Information-theoretic lower and upper bounds on the opponent's success probability are derived, and the lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…That is, reusing the secret key will cause the secret key's information leakage. However, recent research [8,9] about the message authentication (also known as data-origin authentication, which validates a message's integrity and originator [1,2,10,11]) showed that channel noise can help prevent the secret key's information leakage based on Wyner's wiretap channel.…”
Section: Alicementioning
confidence: 99%
See 2 more Smart Citations
“…That is, reusing the secret key will cause the secret key's information leakage. However, recent research [8,9] about the message authentication (also known as data-origin authentication, which validates a message's integrity and originator [1,2,10,11]) showed that channel noise can help prevent the secret key's information leakage based on Wyner's wiretap channel.…”
Section: Alicementioning
confidence: 99%
“…By jointly designing the channel and authentication coding, Eve's success probability can reduce from P ≥ 2 −H(K)/2 to P = 2 −H(K) , since the secret key can be hidden from her by channel noise. Furthermore, our previous work [9] introduced noisy channels into the systematic authentication code and proved that it is more robust and flexible than Simmons's authentication to protect against Eve's attacks. There are two primary differences between message authentication and identity authentication [1,2]: (1) message authentication might not happen in real time, but identity authentication does; and (2) message authentication simply authenticates one message, and the process needs to be repeated for each new message.…”
Section: Alicementioning
confidence: 99%
See 1 more Smart Citation
“…This problem, also referred to as the problem of output approximation, provides a powerful tool to analyze the fundamental limits of various problems in information theory and information security. Some such examples include identification codes [11][12][13], distributed hypothesis testing [14], message authentication [15], secret key generation [16], and coding for secure communication [17][18][19]. We consider two types of problems in which either a general source (mean-channel resolvability) or a VL uniform random number (VL channel resolvability) is used as a coin distribution.…”
Section: Introductionmentioning
confidence: 99%
“…In the next paper [9], entitled "Message Authentication over Noisy Channels", Fanfan Zheng, et al reformulate the authentication problems in "Authentication over noisy channels" in IEEE Trans. Inf.…”
mentioning
confidence: 99%